The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/1678-4499.0120
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de filme de quitosana para o controle de aflatoxinas em amendoim

Abstract: ResumoNeste estudo, verificou-se a utilização de um filme de quitosana para o controle do crescimento e produção de aflatoxinas por A. parasiticus em amendoim. Os filmes foram aplicados sobre os grãos por meio de duas metodologias (aspersão e imersão). Os grãos recobertos foram inoculados com 2,5 ml de uma suspensão contendo 1,0×106 esporos/ml e incubados a 25 o C por 7 dias. A concentração de aflatoxinas foi determinada por cromatografia em camada delgada, utilizando a técnica de densitometria. A verificação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…To date, only a few studies reported the effect of chitosan on both growth and mycotoxin production in different fungal species. For instance, on Aspergillus flavus and Aspergillus parasiticus [37,38,39] and Alternaria alternata f. sp. lycopersici [40].…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few studies reported the effect of chitosan on both growth and mycotoxin production in different fungal species. For instance, on Aspergillus flavus and Aspergillus parasiticus [37,38,39] and Alternaria alternata f. sp. lycopersici [40].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also obtained for spore germination and mycelial growth. SILVA et al (2015) found that the in vivo use of 2% chitosan reduced the spore concentration and the production of Aspergillus parasiticus in peanuts, and promoted, in vitro, morphological changes in the spores, such as swelling, larger diameter (20 μm), and absence of spicules. According to COQUEIRO; DI PIERO (2011), the exact mechanism of action on the pathogen is not yet fully understood.…”
Section: Resultsmentioning
confidence: 98%